Microsoft Exchange 2013 High Availability - Mota, Nuno (Packt Publishing, 2014)
This book is a hands-on practical guide that provides the reader with a number of clear scenarios and examples, making it easier to understand and apply the new concepts. Each chapter can be used as a reference, or it can be read from beginning to end, allowing consultants/administrators to build a solid and highly available Exchange 2013 environment. If you are a messaging professional who wants to learn to design a highly available Exchange 2013 environment, this book is for you. Although not a definite requirement, practical experience with Exchange 2010 is expected, without being a subject matter expert
Description based on publisher supplied metadata and other sources
Keywords: Client/server computing; Electronic mail systems; Microsoft Exchange server